Motivating Millennial Bank Employees in Wenzhou, China from Financial and Non-financial Perspectives - Wang, Yanyu (2022)
As Generation X retires, Millennial professionals are becoming more involved in the workforce. Numerous skilled individuals from the Wenzhou banking industry have migrated to non-banking financial firms, and banks should seriously consider the job satisfaction of Millennial employees (Sun, 2017). This dissertation focuses on how Wenzhou's banking sector may better motivate its entry-level Millennial staff.